Pengaruh Desain Punch Terhadap Mutu Fisik dan Disolusi Tablet MUPS Metformin HCl - Wanda B. Putri; Friesca S. Nurhaidah; Helmy Yusuf; Maria L.A.D. Lestari (PT Dexa Medica, 2023)
The compaction of multi-unit pellet system (MUPS) into tablets is a potential alternative for sustained release drugs. Tableting tools (punch and die) affect the compaction process and quality of MUPS tablets. The punch design intends to preserve the desired drug release of compacted pellets. This study aims to investigate the effect of two punch shapes, the flat face radius edge (FFRE) and concave-faced punch (concave), each at two different cup depths, on the physical properties and release profile of metformin HCl MUPS tablets. Drug release parameters, t50 values, showed that the metformin HCl released from MUPS tablets was faster than the uncompacted sustained release pellets. The similarity of the dissolution profile (f2) between MUPS tablets and uncompacted metformin HCl pellets was lower than 50 as the minimum acceptance value. The tablet tensile strength obtained was below the requirements (<1.7 MPa). Tablet disintegration time was approximately less than 2 minutes. In conclusion, drug release profile of the MUPS tablets showed damage of the pellets due to compaction process. Nevertheless, pellets compacted at low compaction pressure using FFRE with a deeper cup depth (size 0.80 mm) showed a slightly better protection compared to other punch shapes and cup depth sizes applied.